Laparoscopic cholecystectomy delayed by complicated myocardial infarction with papillary muscle rupture, and performed after unique complex mitral repair - Bitner, Miroslaw (Termedia Publishing House, 2013)
A 65-year-old woman was admitted for laparoscopic cholecystectomy, a method of choice for gallbladder diseases. Symptoms of gallstones are similar to angina pectoris, especially in right coronary artery stenosis. In this case, masked by known symptomatic gallstones, unsuspected coronary artery disease manifested with complicated myocardial infarction and pulmonary edema. The patient survived the acute period, treated pharmacologically. Severe mitral insufficiency caused mainly by ruptured papillary muscle, with left ventricle and atrium enlargement, and right coronary artery stenosis were indications for heart surgery. Repair of this infrequent complication of myocardial infarction is rarely feasible. The complex repair, unique for this cause, is described. During the operation, the head of the ruptured posteromedial papillary muscle was re-implanted, and two neo-chords implanted for prolapsing the A2 mitral valve segment. Annuloplasty with a 29 mm elastic ring accomplished repair. Saphenous bypass graft was applied to the only feasible postero-lateral branch. Although intraoperative echocardiography revealed excellent results, inotropic support, and intra-aortic counterpulsation were necessary for weaning off cardio-pulmonary bypass and low cardiac output treatment. The patient was discharged home on postoperative day 12, with anticoagulant administered for 3 months. As soon as it was no longer required, she underwent laparoscopic cholecystectomy, with no complications. Durable results of both operations performed 5 years ago are confirmed by physical examination and ultrasonography. Complex mitral valve repair, rather than valve replacement, should be considered in similar cases. Possibility of coexistence of coronary artery disease should be considered before cholecystectomy. Good quality repair of cardiac disease allows for laparoscopic cholecystectomy.